Pengembangan Permainan Latakar sebagai Media Latihan Karate - Annisa, Ocha Nurul; Kaharina, Arifah (MAN Insan Cendekia Jambi, 2025)
The study aims to develop and produce a suitable, interesting, and student-friendly LATAKAR (Karate Snakes and Ladders) game-based learning medium. This medium is designed to strengthen student engagement and motivation to master basic karate techniques through a fun and interactive approach. The study is a Research and Development (R&D) study using the ADDIE development model. The research population consisted of 80 karate extracurricular students at SDN Lidah Kulon 1/464 Surabaya, with 50 students selected as samples using purposive sampling. The research instruments included a material expert validation sheet, a media expert validation sheet, and a student response questionnaire regarding the product. The data were analyzed descriptively and quantitatively using the feasibility percentage technique. The results showed that the LATAKAR game media obtained an expert validation score of 97.5% (very feasible category) and a student response score of 96.85% (very positive category), with no recommendations for revision from the validators. This media proved to be valid, practical, and interesting for use in karate training in elementary schools because it was able to combine elements of educational games, physical activities, and student character.